Perbandingan Fonologi Bahasa Indonesia dan Bahasa Thailand - Dara Mustika Haris; Putri Febby Febrianti; Meisya Khairunnisa Hanifa (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Research aims to explore the comparison between Indonesian and Thai languages, focusing on structure, phonology, and grammar rules. The methodology involves historical and cultural analysis to understand their influences. Phonetic examination compares pronunciation of phonemes. The study also investigates morphological aspects like word formation, inflection, and affixation. Syntactic analysis examines sentence structures, grammar, and phrase roles. The findings provide a comprehensive overview of linguistic differences, alongside cultural and historical impacts. Implications include contributions to interlanguage understanding, development of teaching methods, and cross-cultural translation. This research serves as a foundation for linguistic practitioners, translators, and language instructors to comprehend and leverage the differences and similarities between both languages.